2002
DOI: 10.1038/nature00838
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of brain dystroglycan recapitulates aspects of congenital muscular dystrophy

Abstract: Fukuyama congenital muscular dystrophy (FCMD), muscle-eye-brain disease (MEB), and Walker-Warburg syndrome are congenital muscular dystrophies (CMDs) with associated developmental brain defects. Mutations reported in genes of FCMD and MEB patients suggest that the genes may be involved in protein glycosylation. Dystroglycan is a highly glycosylated component of the muscle dystrophin-glycoprotein complex that is also expressed in brain, where its function is unknown. Here we show that brain-selective deletion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
472
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 532 publications
(511 citation statements)
references
References 29 publications
37
472
1
1
Order By: Relevance
“…[38][39][40] Admittedly, loss of the entire dystroglycan protein might have effects beyond those caused by defects in its glycosylation, but these data nevertheless support the possibility that all glycosylation defects in the dystroglycanopathies could be centered on dystroglycan. This characterization represents the current state of the literature.…”
Section: Glycosylation Of Dystroglycanmentioning
confidence: 89%
“…[38][39][40] Admittedly, loss of the entire dystroglycan protein might have effects beyond those caused by defects in its glycosylation, but these data nevertheless support the possibility that all glycosylation defects in the dystroglycanopathies could be centered on dystroglycan. This characterization represents the current state of the literature.…”
Section: Glycosylation Of Dystroglycanmentioning
confidence: 89%
“…Such mutations also result in structural and physiological changes within the CNS, revealing an important role for the DGC in brain function. For example, a mutant form of a-dystroglycan results in structural anomalies within the brain and prevents the onset of hippocampal LTP (Moore et al, 2002). Dystro-phin mutants also show abnormal electroretinogram (ERG) profiles (Pillers et al, 1999a,b;Dalloz et al, 2003), and the elimination of Dp71 results in the mislocalization of both Kir4.1 and AQP4 in mouse retina (Connors and Kofuji, 2002;Dalloz et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Protein o-mannose beta-1,2-N-acetylglucosaminyltransferase (PoMGnT1) that was isolated in 2001 16 , is the first human glycosyltransferase which was found to participate in o-mannosyl glycan synthesis in muscle and brain by adding N-acetylglucosamine to O-linked mannose 16 . soon after, Michele et al 17 and Moore et al 18 suggested that, in addition to PoMGnT1, fukutin and acetylglucosaminyltransferase-like protein (lArGe) may participate in a similar pathway "that ultimately results in transfers of sugar to dystroglycan". In patients with FCMD or MeB disease and in dystrophic mice they demonstrated that the o-glycosylation of alpha-DG, mediated by different glycosyltransferases, is essential for muscle and brain development and functions.…”
Section: Fig 1 Schematic Representation Of the Main Proteins Involvementioning
confidence: 99%
“…At last, in 2002 two works from Campbells' research group at the Iowa University 17,18 demonstrated that patients with MeB and FCMD, who carry mutant PoMGnT1 and fukutin genes, respectively, had an abnormal hypo- FCMD: Fukuyama congenital muscular dystrophy; lGMD: limb girdle muscular dystrophy; MDC: muscular dystrophy, congenital; MeB: muscle-eye-brain; PoMGnT1: protein o-manose beta1,2-N-acetylglucosaminyltransferase; WWs: Walker-Warburg syndrome.…”
Section: Disorders Of Glycosylation Of Alphadg (Alpha-dystroglycanopamentioning
confidence: 99%
See 1 more Smart Citation